A systematic literature review of prognostic factors in patients with HR+/HER2− advanced breast cancer in Japan. (21st August 2021) - Hattori, Masaya; Novick, Diego; Takaura, Kana; Tanizawa, Yoshinori; Kawaguchi, Tsutomu; Haro, Josep Maria; Monistrol-Mula, Anna; Onishi, Akira; Iwata, Hiroji
Abstract: Background: Breast cancer is the most prevalent cancer in women in Japan and the fifth in mortality. This systematic review summarized the evidence for prognostic factors for patients with HR+/HER2− advanced and metastatic breast cancer in Japan. Methods: MEDLINE and EMBASE were searched with keywords 'breast neoplasms' AND 'Japan' AND 'advanced' or equivalent, and Japan Medical Abstract Society database with 'breast cancer' AND 'advanced/metastatic' for publications from January 2010 to October 2019. ASCO, ESMO, ABC4 abstracts and WHO website were hand searched. The endpoints of interest were overall survival, progression-free survival, tumour response and post-progression survival. Factors were evaluated based on the consistency in direction and the strength (hazard ratios) of association. Results: Searches identified 4530 publications, of which 27 were eligible. All were observational studies. Among the endpoints, overall survival was the most commonly assessed ( n  = 22) and evaluated further. Ki-67 expression, progesterone receptor expression status, tumour grade and lymph node metastases were consistently associated with poor overall survival in univariate analysis but not in multivariate analysis. Short disease-free interval, the number of metastatic organs and liver metastasis were consistently associated with poor overall survival in both of univariate and multivariate analysis. The association was strong for liver metastasis (hazard ratio ≥2.8 in the majority of studies) and moderate for disease-free interval and the number of metastatic organs (hazard ratio 1.3–2.8 in the majority of studies). Conclusions: Disease-free interval, the number of metastatic organs and liver metastasis were identified as independent prognostic factors for overall survival. These findings may help clinical decision-making to improve outcomes in patients with HR+/HER2− advanced and metastatic breast cancer. Abstract : This systematic review found that disease-free interval, the number of metastatic organs and liver metastasis were independent prognostic factors for overall survival in patients with HR+/HER2− advanced and metastatic breast cancer.